Perspectives on environmental law scholarship : essays on purpose, shape and direction / edited by Ole W. Pedersen, Newcastle University. - Pedersen, Ole W. (Cambridge University Press, 2018)
This collection invites environmental law scholars to reflect on what it means to be an environmental law scholar and to consider how and why environmental law scholars engage in environmental law scholarship. Leading environmental law scholars from different backgrounds and jurisdictions offer their personal reflections on the nature, form, quality and challenges of environmental law scholarship. The collection offers the first honest introspection on what environmental law scholarship is and is not. It considers the unique contributions of environmental law scholarship to legal scholarship more generally, reflecting on what sets environmental law scholarship apart from other disciplines of legal scholarship and the challenges arising from these differences.